Assessing the role of Chemokine (C–C motif) ligand 14 in AKI: a European consensus meeting - Jay L. Koyner; Christian Arndt; Jaume Baldira Martinez de Irujo; Sílvia Coelho; Manuel Garcia-Montesinos de la Peña; Luca di Girolamo; Michael Joannidis; Pablo Jorge-Monjas; Christian Koch; Steven Lobaz; Alain Meyer; Marlies Ostermann; et al. (Renal Failure)
Background Urinary Chemokine (C–C motif) ligand 14 (CCL14) is a biomarker associated with persistent severe acute kidney injury (AKI). There is limited data to support the implementation of this AKI biomarker to guide therapeutic actions.Methods Sixteen AKI experts with clinical CCL14 experience participated in a Delphi-based method to reach consensus on when and how to potentially use CCL14. Consensus was defined as ≥ 80% agreement (participants answered with ‘Yes’, or three to four points on a five-point Likert Scale).Results Key consensus areas for CCL14 test implementation were: identifying challenges and mitigations, developing a comprehensive protocol and pairing it with a treatment plan, and defining the target population. The majority agreed that CCL14 results can help to prioritize AKI management decisions. CCL14 levels above the high cutoff (> 13 ng/mL) significantly changed the level of concern for modifying the AKI treatment plan (p < 0.001). The highest level of concern to modify the treatment plan was for discussions on renal replacement therapy (RRT) initiation for CCL14 levels > 13 ng/mL. The level of concern for discussion on RRT initiation between High and Low, and between Medium and Low CCL14 levels, showed significant differences.Conclusion Real world urinary CCL14 use appears to provide improved care options to patients at risk for persistent severe AKI. Experts believe there is a role for CCL14 in AKI management and it may potentially reduce AKI-disease burden. There is, however, an urgent need for evidence on treatment decisions and adjustments based on CCL14 results.